Education With a Sense of Wonder: A Spiritual Journey - Starratt, Ruth Stuart (Catholic Education: A Journal of Inquiry and Practice, 1999)
The visual arts offer ample opportunities for educators to teach to the soul. This essay opens up some of the possibilities present in art education, opportunities to inspire dreams, announce visions, and ask ultimate questions.